Innovation of Enterprise Resource Planning for Efficiency of Healthcare Management: Migration Data Progress - Romayatul, Liya; Putri Nur Indah Sari; Rafida Alifiyah Yusroh; Muhammad Ganda Saputra (Tarqabin Nusantara Group, 2025)
Data is an important component in a system/software/application. The ERP (Enterprise Resource Planning) system is a business software package system that aims to help companies automate and integrate most business processes, share data and activities within a company, create and access information from the environment in a relevant, accurate and timely manner. This activity is a service program in the form of apprenticeship to partners, namely PT X with a jobdesk in the form of migrating company data into an ERP (Enterprise Resource Planning) system with the aim of forming an ERP (Enterprise Resource Planning) information system that helps the service process be more effective and efficient. This activity was carried out for 6 months, namely July-December 2023. One of the obstacles in the data migration process that took place was speed disturbances in the system, especially if used simultaneously. Implementation of an ERP-based data input process system at PT X can be expected to minimize the occurrence of human error which can result in errors in identifying subsequent data management. So the output obtained will be more accurate.